i-Tube: revolutionise the way of delivering Islamic edutainment content - Ahmad Dahlan, Abdul Rahman; Ahmad Mukhtar, Atiqah; Zahari, Nabihah; Awang, Siti Nurasyikin; Muhammad, Muhd. Rosydi (Research Publish Journals, 2017)
Social video has exploded in the past years and it is an important part of the online experience that grows exponentially. Today, YouTube has become the largest user-driven video content provider in the world; it has become a major platform for disseminating multimedia information. We can see a lot of advantages and disadvantages of this channel. It is a good platform for people to find and share information, reach people globally and also a best marketing platform to promote and sell products. However, there are inappropriate contents in YouTube which pose negative effects to the viewers. As a Muslim, it is an obligation to seek for knowledge and avoid from seeing inappropriate things. This paper proposes an edutainment video platform that adhere to Islamic guidelines and principles. This idea can be a stepping stone for the promotion of Islamic ambience in the context of social network environment.